RENAL ARTERY ANEURYSM – A CASE REPORT FROM KP: Renal Artery Aneurysm – A Case Report From KP - Nasim, Omer; Rustam, Zainab; Khan, Zubair Ahmed; Ahmad, Jamil (Journal of Rawalpindi Medical College, 2023)
Renal artery aneurysm (RAA) is a rare lesion and occurs in less than 1% of the population. There are multiple available treatment options which depend on the type of aneurysm and the timely diagnoses of the condition. Understanding these options is important; endovascular techniques, renal auto-transplantation and nephrectomy maybe indicated. A case of RAA in the left renal artery which was surgically treated with radical nephrectomy because of the nature of the presentation which was an emergency and was managed swiftly to save the patient’s life.